Creative Thinking Skills in Writing Poetry Text at Sekolah Penggerak - Rustam Rustam; Arif Fadillah; Urip Sulistiyo; Riky Nelvia D (STAI Hubbulwathan Duri, 2023)
This study aims to describe students' creative thinking skills in writing pantun texts by means of media images. This type of research is qualitative research conducted by describing and elaborating case studies found in the field. The subject of this research is 30 students in class VII of a Islamic Junior High School in Jambi and one of the Indonesian language teachers. Data collection techniques in this study were observation interviews and documentation. Analysis was carried out using descriptive qualitative research methods. The findings were analyzed and then described descriptively. The questionnaire instrument was used to assess students' writing results in the form of pantun texts. The pantun text is assessed based on predetermined instrument indicators. This instrument makes it easier to determine the suitability of the pantun form that is made. The results obtained in this study, the implementation of pantun learning is carried out based on the teaching modules in the independent curriculum. The creative process is carried out in the form of displaying various images which obtain the final result that students find it easier to find creative vocabulary. The learning process is carried out based on the initial competency components, learning objectives, meaningful understanding, triggering questions, teaching preparation, and assessment. The creative process in writing rhymes in class This is done by observing the display of images on the projector screen and observing the pictures in reading books. Thus students can write rhymes with a variety of creative vocabulary.